Tunanetra’s Parenting on Early Age Children - Arini, Retno; Diana, Diana (Jurusan PGPAUD FIP UNNES, 2019)
This study aimed to describe: (1) the practical application of blind parents’ parenting on early age children, (2) blind parents’ problem during their practical parenting on early age children. This study used a descriptive qualitative approach with the subjects of the study of blind couples who have children aged 6-7 years old, their family members and their neighbors. The method of data collection was gained through observation, interviews and documentation. The data analysis technique used was data reduction, data presentation and conclusion drawing. The data was validated through triangulation technique. The results showed that in parenting practices, blind parents could conduct their role as parents well, for example by providing adequate and nutritious food, accompanying children’s activities such as school, and educating good manners to their children. The problem faced by blind parents during their parenting is when the child is sick. For this problem, they will usually ask for help from those who can see.